2019
DOI: 10.1186/s12870-019-1835-6
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping and genome-wide association study reveal two novel loci associated with green flesh color in cucumber

Abstract: Background Green flesh color, resulting from the accumulation of chlorophyll, is one of the most important commercial traits for the fruits. The genetic network regulating green flesh formation has been studied in tomato, melon and watermelon. However, little is known about the inheritance and molecular basis of green flesh in cucumber. This study sought to determine the main genomic regions associated with green flesh. Three F 2 and two BC 1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Compared with the pale yellow flesh COS, the pale green flesh ZXG01555 showed significantly higher chlorophyll content, indicating a key role of chlorophyll in green flesh formation. The results were consistent with Bo et al., (2019), who reported that cucumber green flesh colour formation resulted from chlorophyll accumulation. Our results revealed that green flesh colour was controlled by a major effective QTL.…”
Section: Discussionsupporting
confidence: 93%
“…Compared with the pale yellow flesh COS, the pale green flesh ZXG01555 showed significantly higher chlorophyll content, indicating a key role of chlorophyll in green flesh formation. The results were consistent with Bo et al., (2019), who reported that cucumber green flesh colour formation resulted from chlorophyll accumulation. Our results revealed that green flesh colour was controlled by a major effective QTL.…”
Section: Discussionsupporting
confidence: 93%
“…To understand the trend of fruit orientation in different pepper populations, identify the possible minor alleles that contribute to the few intermediate phenotypes, and determine the major locus controlling upright and pendent fruit orientations, we performed QTL and GWAS analyses. The combined use of QTLs and GWAS was previously shown to be a powerful approach for the identification of loci and candidate genes in pepper ( Han et al, 2018 ), as well as other crops ( He et al, 2017 ; Liu et al, 2018 ; Zhao et al, 2018 ; Bo et al, 2019 ; Siddique et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…54 ). The green flesh ( gf ) in immature cucumber, results of accumulation of chlorophyll, is controlled by two loci 55 .…”
Section: Genes and Qtl For Fruit–related Traitsmentioning
confidence: 99%